Amine-Coated Carbon Dots (NH2-FCDs) as Novel Antimicrobial Agent for Gram-Negative Bacteria - Devkota, Asmita; Pandey, Anju; Yadegari, Zeinab; Dumenyo, Korsi; Taheri, Ali (Frontiers in Nanotechnology, 2021)
Multi drug resistance (MDR) is a major concern in battling infectious bacterial diseases. The overuse of antibiotics contributes to the emergence of resistance by eradicating the drug-sensitive strains, leaving behind the resistant strains that multiply without any competition. Nanoparticles are becoming popular as novel antimicrobial agents that follow a different mode of actions from standard antibiotics and are therefore desirable against MDR bacteria. In this study, we synthesized carbon dots from different precursors including glucosamine HCL (GlcNH2·HCl) and 4,7,10-trioxa-1,13-tridecanediamine (TTDDA) and studied their antimicrobial effects in a diverse list of gram-negative bacteria including, Escherichia coli, Pseudomonas syringae, Salmonella enterica subsp. enterica serovar Typhimurium, Pectobacterium carotovorum, Agrobacterium tumefaciens and Agrobacterium rhizogenes. We demonstrated the antimicrobial properties of these carbon dots against these bacteria and provided the optimum concentration and incubation times for each bacterial species. Our findings indicated that not all carbon dots carry antimicrobial properties and there is also a variation between different bacterial species in their resistance against these carbon dots.